No evidence of local adaptation of immune responses to Gyrodactylus in three-spined stickleback (Gasterosteus aculeatus). Issue 60 (January 2017) - Robertson, Shaun; Bradley, Janette E.; MacColl, Andrew D.C.
Abstract: Parasitism represents one of the most widespread lifestyles in the animal kingdom, with the potential to drive coevolutionary dynamics with their host population. Where hosts and parasites evolve together, we may find local adaptation. As one of the main host defences against infection, there is the potential for the immune response to be adapted to local parasites. In this study, we used the three-spined stickleback and its Gyrodactylus parasites to examine the extent of local adaptation of parasite infection dynamics and the immune response to infection. We took two geographically isolated host populations infected with two distinct Gyrodactylus species and performed a reciprocal cross-infection experiment in controlled laboratory conditions. Parasite burdens were monitored over the course of the infection, and individuals were sampled at multiple time points for immune gene expression analysis. We found large differences in virulence between parasite species, irrespective of host, and maladaptation of parasites to their sympatric host. The immune system responded to infection, with a decrease in expression of innate and Th1-type adaptive response genes in fish infected with the less virulent parasite, representing a marker of a possible resistance mechanism. There was no evidence of local adaptation in immune gene expression levels. Our results add to the growing understanding of the extent of host-parasite local adaptation, and demonstrate a systemic immune response during infection with a common ectoparasite. Further immunological studies using the stickleback- Gyrodactylus system can continue to contribute to our understanding of the function of the immune response in natural populations. Highlights: Two Gyrodactylus species show markedly different virulence levels irrespective of host origin. Hosts appear adapted to better resist their sympatric parasites. Infection elicits a change in immune gene expression levels. Some changes are specific to the specific host-parasite combination.